Case construction and the goals of criminal process - Smith, David J. (The British journal of criminology, 1997)
McConville, Sanders and Leng (1991) have argued that the police play the dominant role in a process that constructs the suspect population and produces prosecution cases. Whereas the public rhetoric of the law proclaims ideals of fairness and equality, the process of case construction is driven by the values of crime control. By contrast, this article shows that the criminal justice system can neither be understood nor justified except by reference to the goal of crime control, and that the values of crime control and due process are closely intertwined. Policing cannot be understood as having the function of producing convictions: it evidently has much wider goals. It follows from the essential functions of the police that they tend to be beyond the direct control of the law; the challenge for social science is to understand why rules and values relating to due process influence the police in some circumstances and not in others